Pengaruh Guru Pendidikan Agama Kristen Sebagai Komunikator Terhadap Perkembangan Moral Kristen Siswa Di Kelas XI SMK Yayasan Soposurung Balige Tahun Pembelajaran 2023/2024 - Imelda Siahaan; Lasmaria Lumbantobing; Frainskoy Rio Naibaho; Taripar Aripin Samosir; Rusmauli Simbolon (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The research aims to determine the positive influence of PAK teachers as communicators on the Christian moral development of students in class XI of the Soposurung Balige Foundation Vocational School for the 2023/2024 academic year. The research hypothesis is that there is a positive influence between PAK teachers as communicators on the Christian moral development of students in class. Quantitative research methods. The population of all class XI students at Soposurung Foundation Vocational School for the 2023/2024 academic year who are Protestant Christians is 57 people. This research is population research. The research instrument is a closed questionnaire. The results of data analysis obtained: 1) regression equation. 2) The determination test revealed that the influence was 41.34%. 3) Testing the hypothesis obtained tcount=6.168>ttable=2.000, so H0 is rejected and Ha is accepted, namely that there is a positive influence between PAK teachers as communicators on the Christian moral development of class XI students at Soposurung Foundation Vocational School for the 2023/2024 academic year.